The impact of internet addiction on psychological depression: The mediating role of social anxiety and the moderating role of social support - Gao, Jiawei; Tien, Lichu (Edelweiss Applied Science and Technology, 2025)
Excessive internet use among university students has been linked to psychological depression. This study examines the potential relationship between internet addiction and psychological depression using a sample of university students. A total of 2,586 students participated in an empirical analysis conducted through a questionnaire survey. The study further explores the mediating role of social anxiety and the moderating role of social support in this relationship. The results indicate that: (1) Internet addiction has a significant positive effect on psychological depression among Chinese university students; (2) Social anxiety mediates the relationship between internet addiction and psychological depression; (3) Social support moderates the impact of internet addiction on psychological depression. Based on these findings, this study provides strategic support for interventions aimed at reducing internet addiction and psychological depression among university students by enhancing social support and alleviating social anxiety. It also offers valuable theoretical and practical insights into coping and self-regulation strategies to promote students’ overall mental and physical well-being.